A novel population of memory‐activated natural killer cells associated with low parasitaemia in Plasmodium falciparum‐exposed sickle‐cell trait children. Issue 4 (2nd April 2020) - Loiseau, Claire; Doumbo, Ogobara K; Traore, Boubacar; Brady, Jamie L; Proietti, Carla; de Sousa, Karina P; Crompton, Peter D; Doolan, Denise L
Abstract: Objectives: The sickle‐cell trait phenotype is associated with protection from malaria. Multiple molecular mechanisms have been proposed to explain this protection, but the role of the host immune system has been poorly investigated. We hypothesised that cellular immunity to malaria may develop differently in sickle‐cell trait children (HbAS) and children with normal haemoglobin (HbAA) repeatedly exposed to Plasmodium falciparum ( Pf ). Methods: Paired samples collected prior to the Pf transmission season and during the first malaria episode of the ensuing transmission season from HbAS and HbAA children were analysed by multiplex bead‐based assay and comprehensive multi‐dimensional flow cytometry profiling. Results: Cellular immune profiles were enriched in HbAS relative to HbAA children before the start of the Pf transmission season, with a distinct NK subset. These cells were identified as a novel subset of memory‐activated NK cells characterised by reduced expression of the ecto‐enzyme CD38 as well as co‐expression of high levels of HLA‐DR and CD45RO. The frequency of this NK subset before the transmission season was negatively correlated with parasite density quantified during the first malaria episode of the ensuing transmission season. Functional assessment revealed that these CD38 dim CD45RO + HLA‐DR + NK cells represent a important source of IFN‐γ. Conclusion: Our data suggest that this novel memory‐activated NK cell subset may contribute to an accelerated and enhanced IFN‐γ‐mediated immune response and to control of parasite density in individuals with the sickle‐cell trait. This distinct cellular immune profile may contribute to predispose HbAS children to a relative protection from malaria. Abstract : We present the first evidence for host cellular immunity in HbAS‐mediated relative protection from malaria. We identify the key cell population as a novel population of memory‐activated natural killer cells, which are a major source of IFN‐γ and associate with low parasitaemia in sickle‐cell trait children repeatedly exposed to Plasmodium falciparum . Our data suggest that these cells present before the start of the transmission season may contribute to an accelerated and enhanced IFN‐γ‐mediated immune response and to control of parasite density during the first malaria episode of the ensuing season.